2022
DOI: 10.3390/microorganisms10061247
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Is Not Futile: The Role of Quorum Sensing Plasticity in Pseudomonas aeruginosa Infections and Its Link to Intrinsic Mechanisms of Antibiotic Resistance

Abstract: Bacteria use a cell-cell communication process called quorum sensing (QS) to orchestrate collective behaviors. QS relies on the group-wide detection of extracellular signal molecules called autoinducers (AI). Quorum sensing is required for virulence and biofilm formation in the human pathogen Pseudomonas aeruginosa. In P. aeruginosa, LasR and RhlR are homologous LuxR-type soluble transcription factor receptors that bind their cognate AIs and activate the expression of genes encoding functions required for viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 199 publications
(280 reference statements)
0
7
0
Order By: Relevance
“…The signal reaching a threshold concentration is perceived by a sensor system that activates the QS [ 17 ]. The most frequently produced signals from Proteobacteria have been grouped in the class of N-acyl homoserine lactones (N-AHSLs), almost always synthesized through a LuxI-like synthase and perceived through a sensor-regulator system LuxR-like [ 18 ]. In S. maltophilia , the main QS system relies on the Diffusible Signal Factor (DSF) cis-11-methyl-2-dodecenoic acid, which modulates motility, biofilm formation, antibiotic resistance, and virulence [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The signal reaching a threshold concentration is perceived by a sensor system that activates the QS [ 17 ]. The most frequently produced signals from Proteobacteria have been grouped in the class of N-acyl homoserine lactones (N-AHSLs), almost always synthesized through a LuxI-like synthase and perceived through a sensor-regulator system LuxR-like [ 18 ]. In S. maltophilia , the main QS system relies on the Diffusible Signal Factor (DSF) cis-11-methyl-2-dodecenoic acid, which modulates motility, biofilm formation, antibiotic resistance, and virulence [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among other, several genes coding for extracellular proteases are activated by QS in P. aeruginosa PAO1. LasA protease and LasB elastase are the best characterized and the ones that give the name to the LasI-LasR QS system (Simanek and Paczkowski 2022;Schuster et al 2003). Thought both Las and Rhl QS systems upregulate the expression of the corresponding lasA and lasB coding genes, the former is more prevalent than the latter.…”
Section: Second Weekmentioning
confidence: 99%
“…Recent studies concerning the biofilm-forming bacteria suggested the associative effect over the mechanisms of AR of both inflammatory endotoxins/LPS (with intense action in a biofilm formed on tissues) and the expression of the stress genes [ 120 , 121 ]. According to some authors, the QS mechanism and signal molecules are associated with biofilm formation and intrinsic resistance mechanisms in P. aeruginosa , but even environmental factors play a major role in the activation of virulence genes [ 122 ].…”
Section: Resistance Virulence and Bacterial Fitnessmentioning
confidence: 99%